2005
DOI: 10.1097/01.ijg.0000176929.83734.b4
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness Measurement in Clinical Practice

Abstract: Central corneal thickness measurements in this study differed by at least 20 microm in 20% of eyes. This has important implications for risk assessment, management, and follow-up of patients with glaucoma and related disorders. Factors affecting CCT measurement, such as examiner error or true alterations in corneal thickness, require continued investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…However, accuracy of US pachymeters was studied before, and considerable differences in measurements from the same corneas by several US pachymeters from different manufacturers were reported. 31,32 The absence of tear film, the refractive index of the cornea, and US velocity in the cornea may also affect the results. The different operating principles of these two devices may also play a role in this inconsistency.…”
Section: Discussionmentioning
confidence: 98%
“…However, accuracy of US pachymeters was studied before, and considerable differences in measurements from the same corneas by several US pachymeters from different manufacturers were reported. 31,32 The absence of tear film, the refractive index of the cornea, and US velocity in the cornea may also affect the results. The different operating principles of these two devices may also play a role in this inconsistency.…”
Section: Discussionmentioning
confidence: 98%
“…29 Shildkrot et al emphasized the importance of having more than one measurement of CCT for glaucoma patients and recommended repeating not only CCT measurements but also other follow-up parameters. 30 These recent findings increased the importance of CCT, making it of paramount importance to study different nationalities' normative values for CCT. With the appreciation of the significance of CCT, elucidating other factors potentially influencing CCT measurements has gained more attention.…”
Section: Discussionmentioning
confidence: 98%
“…This was for logistical reasons in such a large screening exercise with much data to collect from each individual. Some studies have shown significant variability in CCT measured by ultrasound pachymetry on different occasions, [31][32][33] although others have found a high degree of reproducibility. 34,35 Finally, we cannot be sure that those considered not to have diabetes would all be deemed negative by strict criteria as it was impractical to perform glucose tolerance tests on all subjects.…”
Section: Discussionmentioning
confidence: 99%